Dissemination of Technology for the Use of Biofertilizers and Biopesticides for Women's Farmer Groups : Diseminasi Teknologi Pemanfaatan Agen Hayati Biofertilizer dan Biopestisida Bagi Kelompok Tani Wanita - Sutarman (Universitas Muhammadiyah Sidoarjo, 2022)
The use of chemicals will be increasingly abandoned considering that they can reduce soil fertility, cause environmental pollution, and are often ineffective. The socialization of biological fertilizers and pesticides technology at the Women Farmers Group (KTW)